Efektifitas Manajemen Kurikulum Merdeka di SMKN 1 Sungai Tabuk - Shafa Muthiah; Gilang Dwi Kurniawan; Siti Mulkaf Lailawati; Siti Raisyah; Tri Ananda Setiyani; Puji Nurwidayati; Suhaimi Suhaimi; Muhammad Saleh (Universitas Negeri Malang, 2025)
Abstract: This study examines the effectiveness of the management of the Merdeka Curriculum (Independent Curriculum) at SMKN 1 Sungai Tabuk through a qualitative case study approach. Data collection techniques included semi-structured interviews, observation, and documentation analysis involving the school principal and two teachers at SMKN 1 Sungai Tabuk. The results indicate that the cycle of planning, development, monitoring, and evaluation operates responsively, based on the principles of link and match and human resource empowerment. Planning involves analyzing the needs of students, local potential, and the Business and Industrial World (DUDI) for curriculum relevance. Development engages teachers actively through internal training, external upskilling, and industrial collaboration, enhancing a sense of ownership and improving pedagogical-technical competence. Continuous monitoring employs tiered frequency with participatory supervision, building a reflective culture supported by visionary leadership. Comprehensive evaluation integrates theoretical exams, practical assessments, industrial projects, and feedback from the business sector for accountability and continuous improvement. These findings represent a best practice in overcoming limitations such as inadequate facilities, varying teacher comprehension, and resource imbalances through flexible innovations, including rotational fieldwork (PKL) schedules, elective subjects, and structured character building. This approach successfully produces vocational graduates who are competent, creative, disciplined, and job-ready.. Keywords: Merdeka Curriculum, Curriculum Management, Link And Match, Best Practice Abstrak: Penelitian ini mengkaji efektivitas manajemen Kurikulum Merdeka di SMKN 1 Sungai Tabuk melalui pendekatan kajian kasus kualitatif dengan teknik pengumpulan data wawancara semi-terstruktur, observasi, dan analisis dokumentasi pada kepala sekolah dan dua guru di SMKN 1 Sungai Tabuk. Hasil menunjukkan siklus perencanaan, pengembangan, monitoring, dan evaluasi berjalan responsif berbasis prinsip link and match serta pemberdayaan sumber daya manusia. Perencanaan menganalisis kebutuhan peserta didik, potensi lokal, dan Dunia Usaha dan Dunia Industri (DUDI) untuk relevansi kurikulum. Pengembangan melibatkan guru aktif melalui pelatihan internal, upskilling eksternal, dan kolaborasi industri, meningkatkan rasa kepemilikan serta kompetensi pedagogik-teknis. Monitoring berkelanjutan berfrekuensi berjenjang dengan supervisi partisipatif membangun budaya reflektif didukung kepemimpinan visioner. Evaluasi komprehensif mengintegrasikan ujian teori, praktik, proyek industri, dan umpan balik dunia usaha untuk akuntabilitas serta perbaikan berkelanjutan. Temuan ini bersifat best practice mengatasi keterbatasan sarana, pemahaman guru, dan ketidakseimbangan sumber daya melalui inovasi fleksibel seperti jadwal PKL rotasional, mata pelajaran pilihan, dan pembinaan karakter terstruktur, menghasilkan lulusan vokasi kompeten, kreatif, disiplin, dan siap kerja Kata kunci: Kurikulum Merdeka, manajemen kurikulum, link and match, best practice